FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA STIE SURAKARTA BERINVESTASI DI PASAR MODAL SYARIAH - Selviana Yosa Pafiandika; Arif Nugroho Rachman (Bajang Institute, 2023)
The purpose of this study is to determine whether understanding of investment, minimal capital, risk and technology has an influence on student interest in investing in the Islamic capital market. The sample used consisted of 60 students representing the entire population. Survey data was collected using a questionnaire distributed by purposive sampling technique. The statistical methods used are statistic descriptive, classical assumptions, multiple linear regression, validity and reliability, and hypotheses using the SPSS Statistics 20 application as data processing. This study shows that understanding investment and investment risk has a significant effect on interest in investing in the Islamic capital market, while minimal capital and technology do not have a significant effect on interest in investing in the Islamic capital market.